G120(P) 2 year neurodevelopmental follow up, a quality improvement project: meeting metrics vs delivering quality assessments. (12th March 2018) - Parmar, M; Merchant, N; Beasley, S; Southernwood, P; Sivakumar, B; Narayanan, S
Abstract : Introduction: Neurodevelopmental outcome assessment is a critical aspect of care for high-risk infants and provides basis for benchmarking, early intervention, and endpoints for research studies. Validated tools are recommended to assess neurodevelopment. National Neonatal Audit Programme data (2013) showed 2 year impairment free survival for <30 weeks was 44% but data was available for only 44%. Aim: To improve 2 year neurodevelopmental assessments and correlate developmental scores with risk factors. Methods: Local data(2013) showed 69% compliance to 2 year appointments with zero formal assessments. Using Quality Improvement Tools we planned to improve formal developmental assessements by 50% and 2 year attendances. Appointments were given on discharge, reminders and alerts set up for 18–30 months range. Real time data monitoring with zero latency feedback was used to drive improvement. Bayley Scales of Infant and Toddler Development III (BSID) was used for the assessment. Moderate delay was defined as composite score −2 to −3SD and severe delay <-3SD in any of the domains. Parental feedback was obtained through an anonymous questionnaire using Likert Scale. Questionaire asked about pre-clinic communication, staff attitude, parent understanding and communication of BSID outcomes. Data analysed using Microsoft Excel. Results: Average age at assessments was 24.9 months. Table 1 shows steady improvement in 2 year assessments. DNA rates increased initially in 2015 on introduction of BSID assessments but using iterative PDSA cycles this was brought down to 3% in 2017. Mean(SD) composite scores for cognitive domain was 91.9 (14), motor 86.6 (13.7) and language 86.4 (24.8). 14.8% of children had moderate delay and 8.5% had severe delay. There appears to be a significant correlation with birth weight (p=0.03) and oxygen days (p=0.01) with cognitive domain. Parental feedback was excellent rating the service as 'very good' (5.5/6 on Likert scale). Conclusion: Dedicated administrative services, timely reminders and active management of DNA's improved the attendance and clinic assessments. Identifying key issues, streamlining service efficiency, potentiated an increase in the neurodevelopmental assessments with excellent parental feedback. Correlation with outcomes will allow for improved support in early infancy and facilitate anticipatory guidance and targeted interventions.